2017
DOI: 10.1210/js.2017-00361
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Scarce Resources With Bone Health TeleECHO to Improve the Care of Osteoporosis

Abstract: Osteoporosis is a common condition with serious consequences because of fractures. Despite availability of treatments to reduce fracture risk, there is a large osteoporosis treatment gap that has reached crisis proportions. There are too few specialists to provide services for patients who need them. Bone Health Extension for Community Health Care Outcomes (TeleECHO) is a strategy using real-time ongoing videoconferencing technology to mentor health care professionals in rural and underserved communities to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…A total of three studies analyzed telehealth interventions in health care professionals and reported outcomes. Lewiecki et al [ 16 ] examined the acceptability of TeleECHO and found that self-confidence in 20 domains of osteoporosis care showed substantial improvement. In addition, they determined that TeleECHO can contribute to alleviating the osteoporosis care crisis by leveraging scarce resources; providing motivated practitioners with the skills to provide better skeletal health care, closer to home, with greater convenience; and being lower cost than referral to a specialty center.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of three studies analyzed telehealth interventions in health care professionals and reported outcomes. Lewiecki et al [ 16 ] examined the acceptability of TeleECHO and found that self-confidence in 20 domains of osteoporosis care showed substantial improvement. In addition, they determined that TeleECHO can contribute to alleviating the osteoporosis care crisis by leveraging scarce resources; providing motivated practitioners with the skills to provide better skeletal health care, closer to home, with greater convenience; and being lower cost than referral to a specialty center.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they determined that TeleECHO can contribute to alleviating the osteoporosis care crisis by leveraging scarce resources; providing motivated practitioners with the skills to provide better skeletal health care, closer to home, with greater convenience; and being lower cost than referral to a specialty center. Additionally, TeleECHO can be applied to any location worldwide with internet access, allowing access in local time zones and a variety of languages [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…The response rate was also as low as 7% of participants, suggesting self-selection bias. 37 The one recorded cluster RCT, by Eaton and colleagues, 26 did not find a benefit of EELM in terms of provider knowledge or perceived competence.…”
Section: Discussionmentioning
confidence: 95%
“…Project ECHO (Extension for Community Healthcare Outcome) is a distance health educational model that uses videoconferencing technology to connect care providers across multiple geographical settings and areas of expertise. 9,10 After conducting a needs assessment to identify knowledge gaps of dialysis providers, we envision creating a forum in which a high-performing home dialysis center will act as "host" institution and provide clinical expertise in home dialysis through a multidisciplinary team. 11 Most home dialysis teams consist of nephrologists, home dialysis nurses and technicians, social workers, dietitians, and dialysis technicians.…”
Section: Action Itemsmentioning
confidence: 99%